Eksistensi Kelembagaan Badan Permusyawaratan Desa (BPD) Desa Sukaramai Kabupaten Kampar Dalam Perspektif Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Gurning, Irwan Toni; Indra S, Mexsassai; Zulwisman, Zulwisman (Peneliti.net, 2024)
The Village Consultative Body functions to establish village regulations together with the village head, accommodate and channel community aspirations. Based on these problems, the author is interested in knowing the existence of the Village Consultative Body (BPD) of Sukaramai Village, Kampar Regency and the inhibiting and supporting factors of the Village Consultative Body (BPD) of Sukaramai Village, Kampar Regency in carrying out its duties and authority. The research method in this thesis uses a type of sociological legal research, namely research on the effectiveness of law in society. The nature of this thesis research is researchdescriptivewhich systematically describes the facts and characteristics of the object being studied accurately. The data collection technique in this research is the interview method and literature review, then after the data is collected it is then analyzed to draw conclusions. Based on the research results, it can be understood that the existence of the Village Consultative Body (BPD) in Village government has existed since the enactment of the Regional Government Law under the Law on Villages which is in effect to date. Together with the Village Head, the BPD carries out government functions as a partner of the Village Government in supervising the running of the Village Government. In reality, the existence of many Village Consultative Bodies themselves have not carried out their roles and functions. Based on the research results, it shows that the Village Consultative Body (BPD) of Sukaramai Village in carrying out its functions of establishing village regulations, monitoring and accommodating community aspirations has not been optimal in its implementation due to a lack of understanding by BPD members of their duties and functions based on applicable regulations. The factors that influence the existence of the Sukaramai Village Deliberative Body are the first, the Inhibiting Factors, namely Facilities, Not understanding its function, the Community not understanding the function of the BPD and the Community, secondly the Supporting Factors, namely the Collaborative Relationship with the village government, the BPD member selection system and Income/Incentives. The efforts made by the Sukaramai BPD in carrying out its duties and functions include efforts from parties outside the BPD, namely those carried out by the Kampar Regency Government and efforts made by the Sukaramai Village BPD.